Whole Blood Transcriptome Analysis in Dairy Ewes Fed a Dietary Grape Pomace Supplementation - Andrea Ianni; Francesca Bennato; Camillo Martino; Maria Antonietta Saletti; Francesco Pomilio; Giuseppe Martino (Veterinary Sciences, 2024)
The present study aims to evaluate the effect of a dietary supplementation with 10% grape pomace (GP) on the whole blood transcriptome of lactating ewes. By applying a log2FC higher than 0.5 or lower than −0.5 and a false discovery rate (FDR) <0.05, the down-regulation of genes coding for plexin C1, ethanolamine kinase 1, tax1-binding protein 1, transmembrane 9 superfamily member 2, and Beclin-1 was observed in animals that received the dietary supplementation. This aspect was also accompanied by a reduction in the blood activity of matrix metalloproteinase 9 (MMP-9; p < 0.05), a gelatinase commonly involved in both acute and chronic pathological events. The ELISA test on other factors involved in inflammatory processes, interleukin 1 (IL-1) and tumor necrosis factor α (TNF-α), as well as in the antioxidant response, glutathione peroxidase (GPx), and catalase (CAT), did not reveal any significant changes (p > 0.05). Overall, the introduction of GP in the diet of ewes gave indications of greater efficacy in preserving animal welfare, with interesting cues regarding the valorization of a by-product with a high biological value.